A method to set the target on-centre steering force characteristic. (October 2016) - Dang, Jianmin; Chen, Hui; Li, Qi; Watanabe, Takeshi; Hayama, Ryouhei; Lou, Liming
In this paper, a method to set the target on-centre steering force characteristic is described. First, both the linear correlations and the non-linear correlations between subjective evaluations and objective metrics were established. During this process, subjective and objective evaluation tests regarding the on-centre steering force characteristic were conducted on a moving-base driving simulator by 15 experienced drivers. To ensure the reliability of the subjective ratings, a method to evaluate the ratings was introduced. Then the linear correlations and the non-linear correlations were analysed using multiple linear regression analysis and a neural network respectively. Second, by setting the desired subjective ratings as an optimization goal, target objective metrics were obtained on the basis of either the linear correlations or the non-linear correlations by means of non-linear programming. The target on-centre steering force characteristic was therefore designed on the basis of the target objective metrics. The results showed that the target on-centre steering force characteristic obtained from the linear correlations was quite similar to that obtained from the non-linear correlations. Also, it was verified that the target on-centre steering force characteristic matched the drivers' preferences. From the correlations and the target on-centre steering force characteristic, engineers can establish the ratings of subjective evaluations and determine how to design the system to meet the target during the virtual design process. It shows a great potential in assisting the engineers to design a good steering feel at the early stages of the development process. Furthermore, the feasibility of this proposed method to allow customers to customize the on-centre steering force characteristic was explored. During this process, a fixed-base driving simulator was used instead of a moving-base driving simulator for cost reasons.